Design and optimization of the ring oscillator based injection locked frequency dividers. (February 2018) - Qiu, Qi-Lin; Yu, Xiao-Peng; Sui, Wen-Quan; Yeo, Kiat-Seng
Abstract: In this paper, the large signal operation of the ring oscillator based injection locked frequency divider is analyzed considering the trade-offs among the operating frequency, locking range and power consumption. A large signal model is used to reveal several key findings such as voltage-limited locking ranges and asymmetry between the upper and lower locking bands. They are applied to the optimize the dividers maintaining a good balance among design considerations. Several prototypes, including the divide-by-2 with 3 and 5 stages of inverters, divide-by-3 and divide-by-5, are implemented in a standard 0.18 µm CMOS technology to verify the operation under a large injected signal. As an extension, dual-modulus prescalers are further designed by the integration of switches for different ways of signal mixing. Measurements results show the proposed divide-by-2/3 unit and a divide-by-8/9 with this unit are able to work up to 8 GHz and 4.0 GHz with maximum power consumption of 0.7 mW and 1.5 mW respectively.